انعكاسات الخوف من الفشل على الثقة بالنفس لدى لاعبي كرة القدم - بن منصورة محمد الصغير (My University, 2024)
ملخص : عنـوان الدراسـة: انعكاسات الخوف من الفشل على الثقة بالنفس لدى لاعبي كرة القدم دراسة ميدانية على مستوى اندية الجهوي الاول لكرة القدم رابطة – عنابة-  اهـدف الدراسـة:  ابراز انعكاس الخوف من الشعور بالخجل والحرج على الثقة بالنفس لدى لاعبي كرة القدم.  تحديد انعكاس الخوف من التقليل من تقدير الذات على الثقة بالنفس لدى لاعبي كرة القدم.  معرفة انعكاس وجود مستقبل غامض على الثقة بالنفس لدى لاعبي كرة القدم.  التعرف على حالة فقدان الاهتمام من الآخرين على الثقة بالنفس لدى لاعبي كرة القدم.  التعرف على انعكاس الخوف من فقدان اهتمام اشخاص مهمين على الثقة بالنفس لدى لاعبي كرة القدم.  فرضـيات الدراسـة:  للخوف من الشعور بالخجل والحرج انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من التقليل من تقدير الذات انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من وجود مستقبل غامض انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من فقدان الاهتمام من الآخرين انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من فقدان اهتمام اشخاص مهمين انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  إجـراءات الدراسـة الميدانيـة:  العينـة: تم اخذ 16 فريق ينشطون على مستوى اندية الجهوي الاول لكرة القدم رابطة عنابة أكابر "ذكور" تم اختيارهم بطريقة قصدية. المجـال الـزماني: امتد المجال الزماني لدراستنا من 15 نوفمبر 2023 إلى غاية 10 ماي 2024.  المجال المكاني: تمت الدراسة على اندية الجهوي الاول لكرة القدم رابطة عنابة أكابر "ذكور".  المنهـج المستخـــدم: تم إستخدام المنهج الوصفي المسحي.  الأدوات المستعملـــة: إعتمدنا في دراستنا على مقياس الخوف من الفشل للاعبين (الرياضيين).  النتائج المتـوصل إلـيها: لقد تم التوصل إلى النتائج التالية:  للخوف من الشعور بالخجل والحرج انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من التقليل من تقدير الذات انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من وجود مستقبل غامض انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من فقدان الاهتمام من الآخرين انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  للخوف من فقدان اهتمام اشخاص مهمين انعكاس على الثقة بالنفس لدى لاعبي كرة القدم.  إستخـلاصات واقتراحــات:  تطوير برامج تدريبية مخصصة تستهدف تعزيز الثقة بالنفس لدى اللاعبين تشمل هذه البرامج تمارين عملية وجلسات نقاش وتوجيهات فردية مصممة لتعزيز الايجابية الذاتية وتحفيز اللاعبين على تحقيق النجاح.  القيام بجلسات التوجيه النفسي والاستشارة لمساعدة اللاعبين في التعامل مع مشاعر الخوف وتعزيز الثقة بأنفسهم.  تحفيز اللاعبين على تطوير نمط تفكير إيجابي يركز على الإيمان بالقدرات الشخصية والتركيز على النجاحات السابقة بدلاً من التركيز على الأخطاء والفشل. abstract ; Study Title: The Implications of Fear of Failure on the Self-Confidence of Football Players: A Field Study at the Level of the First Regional Football Clubs Association – Annaba  Study Objective:  Highlight the reflection of the fear of feeling ashamed and embarrassed about the self-confidence of football players.  Identify the impact of fear of low self-esteem on the self-confidence of football players.  Knowing the impact of having an uncertain future on the self-confidence of football players.  Recognize the case of loss of interest from others on the self-confidence of football players.  Recognize the reflection of the fear of losing the interest of important people on the self-confidence of football players.  Hypotheses of the study:  Fear of shame and embarrassment is a reflection on the self-confidence of footballers.  Fear of low self-esteem is a reflection on soccer players' self-confidence.  Fear of an uncertain future is a reflection on the self-confidence of footballers.  The fear of losing interest from others is a reflection on the self-confidence of footballers.  The fear of losing the interest of important people is a reflection on the self-confidence of football players.  Field Study Procedures:  Sample: 16 teams active at the level of the clubs of the first regional football association Annaba Akbar "males" were selected in an intentional manner. Time domain: The time domain of our study extended from November 15, 2023 to May 10, 2024.  Spatial field: The study was conducted on the clubs of the first regional football association Annaba Akbar "Males".  The method used: The descriptive survey method was used.  Tools used: In our study, we used the Fear of Failure Scale for players (athletes).  Findings: The following findings have been made:  Fear of shame and embarrassment is a reflection on the self-confidence of footballers.  Fear of low self-esteem is a reflection on soccer players' self-confidence.  Fear of an uncertain future is a reflection on the self-confidence of footballers.  The fear of losing interest from others is a reflection on the self-confidence of footballers.  The fear of losing the interest of important people is a reflection on the self-confidence of football players.  Conclusions and Suggestions:  Developing customized training programs aimed at enhancing players' self-confidence. These programs include practical exercises, discussion sessions and individual guidance designed to enhance self-positivity and motivate players to achieve success.  Conducting psychological guidance and counseling sessions to help players deal with feelings of fear and enhance their self-confidence.  Motivate players to develop a positive thinking style that focuses on believing in personal abilities and focusing on past successes rather than on mistakes and failures. résumé ; Titre de l'étude : Les répercussions de la peur de l'échec sur la confiance en soi chez les joueurs de football : Une étude de terrain au niveau des clubs régionaux de première division de la Ligue de Football de Annaba Objectifs de l'étude : • Mettre en évidence l'impact de la peur de la honte et de l'embarras sur la confiance en soi chez les joueurs de football. • Déterminer l'impact de la peur de la diminution de l'estime de soi sur la confiance en soi chez les joueurs de football. • Comprendre l'impact de l'incertitude quant à l'avenir sur la confiance en soi chez les joueurs de football. • Identifier l'impact de la perte d'intérêt des autres sur la confiance en soi chez les joueurs de football. • Identifier l'impact de la peur de perdre l'intérêt des personnes importantes sur la confiance en soi chez les joueurs de football. Hypothèses de l'étude : • La peur de la honte et de l'embarras a un impact sur la confiance en soi chez les joueurs de football. • La peur de la diminution de l'estime de soi a un impact sur la confiance en soi chez les joueurs de football. • La peur de l'incertitude quant à l'avenir a un impact sur la confiance en soi chez les joueurs de football. • La peur de perdre l'intérêt des autres a un impact sur la confiance en soi chez les joueurs de football. • La peur de perdre l'intérêt des personnes importantes a un impact sur la confiance en soi chez les joueurs de football. Procédures de l'étude de terrain : • Échantillon : 16 équipes évoluant au niveau des clubs régionaux de première division de la Ligue de Football de Annaba, seniors masculins, ont été sélectionnées de manière intentionnelle. • Période : La période de notre étude s'étend du 15 novembre 2023 au 10 mai 2024. • Lieu : L'étude a été menée au sein des clubs régionaux de première division de la Ligue de Football de Annaba, seniors masculins. Méthodologie utilisée : La méthode descriptive et l'enquête par sondage ont été utilisées. Outils utilisés : Nous avons utilisé dans notre étude l'échelle de mesure de la peur de l'échec pour les athlètes. Résultatsobtenus : • La peur de la honte et de l'embarras a un impact sur la confiance en soi chez les joueurs de football. • La peur de la diminution de l'estime de soi a un impact sur la confiance en soi chez les joueurs de football. • La peur de l'incertitude quant à l'avenir a un impact sur la confiance en soi chez les joueurs de football. • La peur de perdre l'intérêt des autres a un impact sur la confiance en soi chez les joueurs de football. • La peur de perdre l'intérêt des personnes importantes a un impact sur la confiance en soi chez les joueurs de football. Conclusions et suggestions : • Développer des programmes de formation spécifiques visant à renforcer la confiance en soi chez les joueurs, incluant des exercices pratiques, des sessions de discussion et des orientations individuelles conçues pour renforcer la positivité et motiver les joueurs à réussir. • Organiser des sessions de conseil et d'orientation psychologique pour aider les joueurs à gérer leurs sentiments de peur et renforcer leur confiance en eux. • Encourager les joueurs à développer une mentalité positive en se concentrant sur la croyance en leurs capacités personnelles et en mettant l'accent sur leurs succès passés plutôt que sur leurs erreurs et échecs.
Keywords: الخوف من الفشل; الثقة بالنفس; Fear of failure; Self-confidence; • Peur de l'échec; • Confiance en soi